整合學習共同體於差異化教學的改革 Integrating the Practice of Learning Community into Differentiated Instruction for Instructional Changes - 游自達 Tzu-Ta Yiu; 林素卿 Su-Ching Lin (National Changhua University of Education, 2014)
因應學習者的個別差異進行教學調整，使每個學習者的潛能獲得最大的開展乃是適性教育的核心理念，也是教育工作者長時間關心的議題。｢差異化教學｣與｢學習共同體｣可說是因應個別差異以提升學習品質的二個教學模式。二者之理念與做法有其相近之處，亦各有其獨特性。探討｢差異化教學｣與｢學習共同體｣的理念與做法，發展面對多元特質差異學習者的可能做法，將有助於實踐適性教學，落實教育機會均等的理想。本文乃從差異內涵與理念的分析出發，探討｢差異｣的內涵和因應做法的歷史變遷，再比較學習共同體與差異化教學的理念與做法，最後探討以學習共同體學習辯證的做法為架構，整合於差異化教學的可能途徑。 Actively responding to student's individual differences to enlarge their chance of success is one of the major concerns of educational practitioners. With the philosophy and practical strategies of school reform toward learning community, Manabu Sato promotes an idea of active, collaborative and reflective learning at classroom for education excellence. Differentiated instruction, which is an instruction strategy to enhance individual student's learning by adjusting the content, process, or product of teaching and learning has received increased attention over the past two decades. These two approaches of instruction provide different perspectives to meet individual learning needs and maximize the chance of success. For the purpose of promoting instructional changes for meeting students' characteristics and learning needs, this article aims at integrating the practice of learning community into differentiated instruction. The rationale and instruction practices of learning community and differentiated instruction were first analyzed. The ideas of school as learning community and learning as a practice in dialogue were also discussed. It is suggested that three aspects of dialogic communication in the learning practice can be used as a framework for the integration of learning community and differentiated instruction.